Current topics in astrofundamental physics: primordial cosmology : [proceedings of the NATO Advanced Study Institute on Current Topics in Astrofundamental Physics: Primordial Cosmology, Erice, Italy, 4-15 September 1997] - Sanchez, Norma; Zichichi, Antonino (NATO ASI series / C, 1998)
The present book provides an up-to-date, fundamental and deep understanding of current progress and problems in the study of the early universe, cosmic microwave background radiation, large-scale structure, the dark matter problem. The emphasis is on the mutual impact of fundamental physics and cosmology at both theoretical and experiments/observational levels. The very nature of the subject area calls for the study of different aspects, using different approaches and points of view. However, the book provides a well-defined programme and a global, unifying view, bringing together experimentalists and theoreticians, physicists, astrophysicists and astronomers from a variety of backgrounds. The lectures range from a motivation and pedagogical introduction for students and those not directly working in the field, to the latest developments and the most recent results